Narrative and the triune reality examining Robert W. Jenson's doctrine of the trinity with reference to Eberhard Jüngel - Kwok, Wai Luen (Pickwick Publications, 2022)
Robert Jenson is commended as one of the greatest American theologians in the twentieth century. This book proposes a critique of Jenson's narrative Trinitarianism by comparing it with Eberhard Jungel's theology. It argues for the importance of the double dimensions of event and communicative-linguistics of the Divine narrative